THE EFFECT OF VILLAGE FUNDS AND VILLAGE FUND ALLOCATIONS ON POVERTY RATE IN TOJO UNA-UNA DISTRICT - Harsita, Julianda Megah; Nurdin, Djayani; Kasim, Muhammad Yunus (Master of Management Study Program, Faculty of Economics and Business, Tadulako University, 2025)
This study primarily aims to identify the individual and combined effects of the Village Fund and its distribution on the poverty rate in Tojo Una-Una Regency. This quantitative research uses secondary data collected from various institutions: (1) the Community and Village Empowerment Office of Tojo Una-Una District, the Central Bureau of Statistics, and the Social, Women's Empowerment, and Child Protection Office. The data cover the years from 2020 to 2023. For analysis, we used multiple linear regression with variables including village budget allocation (X2), poverty (Y), and classical assumption testing (X1). (2) The F test results show that the poverty rate is significantly affected by the amount of funds allocated to the village and their distribution, with an F value of 10.362 and a significance level of 0.001 *< 0.05*. The t-test indicates that the village fund variable moderately reduces the poverty rate, with a coefficient of -0.085 and a significance level of 0.017 *< 0.05*. (3) A statistically significant adverse effect on the poverty rate is observed with a coefficient of -0.381 and a significance level of 0.001 *< 0.05*, suggesting that the village fund distribution variable is a key factor